A new resource for the development of SSR markers: Millions of loci from a thousand plant transcriptomes1. (16th June 2016) - Hodel, Richard G. J.; Gitzendanner, Matthew A.; Germain‐Aubrey, Charlotte C.; Liu, Xiaoxian; Crowl, Andrew A.; Sun, Miao; Landis, Jacob B.; Segovia‐Salcedo, M. Claudia; Douglas, Norman A.; Chen, Shichao; Soltis, Douglas E.; Soltis, Pamela S.
Abstract : Premise of the study: The One Thousand Plant Transcriptomes Project (1KP, 1000+ assembled plant transcriptomes) provides an enormous resource for developing microsatellite loci across the plant tree of life. We developed loci from these transcriptomes and tested their utility. Methods and Results: Using software packages and custom scripts, we identified microsatellite loci in 1KP transcriptomes. We assessed the potential for cross‐amplification and whether loci were biased toward exons, as compared to markers derived from genomic DNA. We characterized over 5.7 million simple sequence repeat (SSR) loci from 1334 plant transcriptomes. Eighteen percent of loci substantially overlapped with open reading frames (ORFs), and electronic PCR revealed that over half the loci would amplify successfully in conspecific taxa. Transcriptomic SSRs were approximately three times more likely to map to translated regions than genomic SSRs. Conclusions: We believe microsatellites still have a place in the genomic age—they remain effective and cost‐efficient markers. The loci presented here are a valuable resource for researchers.